Policy Gaps and Challenges in Promoting Inclusive Education in Higher Education Institutions - Ufi Ruhama'; Hamdil Mukhlishin; Ryani Yulian; Sucy Febrianti; Intan Khairunissa (LPPM Undiksha, 2025)
The government has regulated inclusive education across all sectors, including higher education. However, a significant gap between policy and practice persists. This study aims to examine the current state of inclusive education in higher education institutions in Pontianak City, analyze institutional challenges, identify student-related barriers, and explore stakeholders’ perceptions of policy implementation. This study employed a mixed-methods approach, integrating policy analysis, structured interviews, and surveys. Data were collected through document analysis instruments, interviews, and survey questionnaires. The research sample was selected purposively and involved five private higher education institutions, with respondents consisting of lecturers and students, including universities that have received Assistive Technology support from the Ministry of Education, Culture, Research, and Technology. Qualitative data were analyzed using micro-interlocutor analysis and thematic analysis, while quantitative data were processed using descriptive and inferential statistics. The findings indicate that several private universities in Pontianak continue to face limitations in infrastructure, insufficient training for lecturers and staff, and a lack of inclusive teaching and learning materials. These results suggest that inclusive education in higher education requires more than policy formulation alone; it demands a stronger institutional framework to ensure effective implementation. The implications of this study highlight the need for more robust frameworks, relevant professional development, and accessible facilities to bridge the gap between inclusive education policies and their practical implementation in higher education institutions.